Peran Bunda PAUD Dalam Mewujudkan Pengembangan Anak Usia Dini Holistik Integratif di Kabupaten Semarang - Daniswara, Bagas Arika (Jurnal Ilmiah Wahana Pendidikan, 2024)
The role of PAUD mothers plays an important role in improving integrative holistic services. The aim of this research is to describe the role of PAUD mothers in realizing holistic, integrative early childhood development in Semarang Regency. This research uses a qualitative approach. The research subjects who were sources of information were the PAUD Mother Working Group as key informants and the Chair of HIMPAUDI Semarang Regency and the Principal of Smart Children's PAUD School as informants. The data collection techniques used were observation, interviews and documentation. For data validity, source triangulation is used. Data analysis techniques with stages of data collection, data reduction, data presentation, and drawing conclusions. The results of this research show that there are five roles of PAUD mothers in realizing integrative holistic early childhood development, namely: 1) conducting visits to various institutions; 2) developing PAUD institutions in villages, 3) providing motivation to education staff, 4) helping PAUD institutions to participate in accreditation programs, and 5) providing assistance to institutions that support holistic, integrative PAUD. Conclusion This research shows that the role of PAUD mothers in realizing holistic, integrative early childhood development is by conducting visitations and providing motivation to education staff. Supporting factors for the role of PAUD mothers are the implementation of Aphodi Technical Guidance, playing with PAUD mothers, and visits to institutions in remote areas. The inhibiting factors are schedule constraints and APBD budget limitations. Suggestion: the APBD budget needs to be increased further according to needs and regular meetings need to be held with all institutions in Semarang Regency.